2005
DOI: 10.1029/2004ja010634
|View full text |Cite
|
Sign up to set email alerts
|

Annual and semiannual variations of the location and intensity of large‐scale field‐aligned currents

Abstract: The present study examines seasonal variations of large‐scale field‐aligned current (FAC) systems in terms of the dipole tilt and clock angles. Magnetic field measurements from the DMSP F7 and F12‐F15 satellites are used. This data set consists of a total of ∼185,000 auroral oval crossings, out of which ∼121,000 crossings were selected for the present analysis. Focus is placed on the latitude at the demarcation between the region 2 (R2) and region 1 (R1) currents and the intensities of these currents. It is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
66
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 45 publications
17
66
1
Order By: Relevance
“…Ohtani et al (2005b) extended this analysis and showed that the dayside Region 1 current intensity varies by a factor of 2 to 3 over the entire dipole tilt angle range. They also showed that the seasonal variation of the nightside FACs was more complicated with the nightside Region 2 current intensity more intense during winter than in summer.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Ohtani et al (2005b) extended this analysis and showed that the dayside Region 1 current intensity varies by a factor of 2 to 3 over the entire dipole tilt angle range. They also showed that the seasonal variation of the nightside FACs was more complicated with the nightside Region 2 current intensity more intense during winter than in summer.…”
Section: Introductionmentioning
confidence: 94%
“…The seasonal differences in the FAC patterns might suggest effects related to the Earth's dipole tilt angle, location of the OCFLB or effects related to solar illumination and the distribution of ionospheric conductivity over the polar regions. Ohtani et al (2005b) suggested that the seasonal change in the geomagnetic field configuration may explain the poleward shift in the location of the dayside FACs in summer compared with winter since the dayside R1 currents are thought to be located near the OCFLB. In order to investigate this we have overlayed on each FAC map an average OCFLB estimated from the Tsyganenko and Sitnov (2005) TS05 magnetic field model for the mean IMF and solar wind conditions associated with the events used in constructing each FAC map.…”
Section: Summary Of Seasonal Fac Observationsmentioning
confidence: 99%
See 3 more Smart Citations